Clinical performance of class I cavities restored with bulk fill composite at a 1-year follow-up using the FDI criteria: a randomized clinical trial - Chinni Suneelkumar; Puttaganti Harshala; Koppolu Madhusudhana; Anumula Lavanya; Anirudhan Subha; Sannapureddy Swapna (Restorative Dentistry & Endodontics, 2021)
ObjectivesThe present study aimed to evaluate the survival rate and clinical performance of class 1 composite restorations restored with the Filtek Bulk Fill composite material using either the bulk fill technique or the incremental technique at baseline (1 week) and at 3, 6 and 12 months of follow-up.Materials and MethodsForty-two patients with at least 2 carious teeth were selected. Following randomization, one tooth was restored with the Filtek Bulk Fill composite using the incremental fill technique, and the other tooth was restored with the same material using the bulk fill technique. Patients were recalled for follow-up at baseline (1 week) and 3, 6, and 12 months and evaluated using the FDI criteria.ResultsThe data were analyzed using the McNemar χ2 test. No statistically significant differences were found between the scores of teeth restored with either technique. At baseline and at 3, 6, and 12 months of follow-up; there were no significant difference in the clinical status of both groups of restorations.ConclusionsWithin the limitations of this study, using the bulk fill technique for restorations with the Filtek Bulk Fill material seems to be equally efficient to using the incremental fill technique.Trial RegistrationClinical Trials Registry-India Identifier: CTRI/2017/07/008961